2020
DOI: 10.3390/vaccines8010110
|View full text |Cite
|
Sign up to set email alerts
|

Effective Activation of Human Antigen-Presenting Cells and Cytotoxic CD8+ T Cells by a Calcium Phosphate-Based Nanoparticle Vaccine Delivery System

Abstract: The ability of vaccines to induce T cell responses is crucial for preventing diseases caused by viruses. Nanoparticles (NPs) are considered to be efficient tools for the initiation of potent immune responses. Calcium phosphate (CaP) NPs are a class of biodegradable nanocarriers that are able to deliver immune activating molecules across physiological barriers. Therefore, the aim of this study was to assess whether Toll-like receptor (TLR) ligand and viral antigen functionalized CaP NPs are capable of inducing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…A previous study revealed the requirement of CD28 costimulation for the proliferation of exhausted T cells after PD-1-targeted therapy (22). We have recently described that CpG-functionalized CaP NPVs efficiently activate APCs, indicated by increased expression of the costimulatory B7 molecules CD80 and CD86 after in vitro and in vivo stimulation (8,23,24). Interestingly, activation of APCs was still enhanced in the spleen 7 days after immunization, possibly due to endocrine or paracrine effects.…”
Section: Resultsmentioning
confidence: 92%
“…A previous study revealed the requirement of CD28 costimulation for the proliferation of exhausted T cells after PD-1-targeted therapy (22). We have recently described that CpG-functionalized CaP NPVs efficiently activate APCs, indicated by increased expression of the costimulatory B7 molecules CD80 and CD86 after in vitro and in vivo stimulation (8,23,24). Interestingly, activation of APCs was still enhanced in the spleen 7 days after immunization, possibly due to endocrine or paracrine effects.…”
Section: Resultsmentioning
confidence: 92%
“…Single studies on osseous macrophages revealed that CaP-NPs enhanced inflammation by modulating macrophages while osteogenesis was attenuated (26). Other studies could show that CaP-NPs lead to maturation of antigen presenting cells, cytokine secretion and activation of cytotoxic T cells resulting in a strong immune response (9). Natural killer cells (NK cells) are among the first cells to interact with applied nanoparticles as these innate immune cells can act without prior sensitization.…”
Section: Discussionmentioning
confidence: 99%
“…They served as carriers for antibiotics and have been applied for vaccination and immunization against infectious diseases successfully (8). In contrast to other nanoparticle-preparations, CaP-NP can be loaded with various immune activating components at flexible dosages simultaneously, which optimizes and individualizes the immune response (9). Taken up by dendritic cells CaP-NPs were able to induce a strong immunization in vivo and showed efficiency against experimental retroviral infections (10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As carriers, CaP nanoparticles can load antigens at different time points through encapsulation during the particle formation or passive adsorption after particle formation [ 45 ]. Compared with soluble Toll-like receptor (TLR) ligands, TLR ligand and viral antigen functionalised CaP nanoparticles are effective in inducing the efficient maturation of human APCs [ 49 ], as indicated by increase in the levels of co-stimulating molecules and the secretion of proinflammatory cytokines, which cause the remarkable expansion of virus-specific T cells. Another similar design confirmed this conclusion in mice [ 50 ].…”
Section: Nanoparticles As Vaccine Adjuvants In Antiviral Infectionmentioning
confidence: 99%